Assessment of patterned membrane in a tilted panel filtration system for fouling control in activated sludge filtration - Osman, W.N.A.W. (Institute of Physics Publishing, 2020)
Membrane bioreactor (MBR) is a combination between advanced membrane filtration system and activated sludge biological treatment for sewage effluents treatment. Despite demonstrating a remarkable advantage over the conventional activated sludge process, MBR is still limited by the occurrence of membrane fouling problem, which reduces the performance and lifespan of the membrane causing higher maintenance and operation costs. Finding sustainable membrane fouling mitigation strategies has become the main concern in MBR operation. Hence, air bubbling method had been proven as one of the membrane fouling mitigation strategies. Ineffective air bubbling contributes to higher energy consumption for MBR operation. It must be pumped at high rates as low rates air bubbles only show poor contacts with the membrane surface in which limits its efficacy to scour-off the foulant. In this study, the performance of a patterned membrane in a tilted panel system was systematically evaluated to enhance air bubble effectiveness for membrane fouling control in activated sludge filtration. The patterned surface topography in a combination of the tilted panel is expected to enhance air bubbles contacts and increase their fouling control roles. An imprinting step was included into the fabrication procedure in order to create membrane with patterned surface. Results showed that the patterned outperform flat membrane in both tilted and vertical systems. Such an advantage can be ascribed by both the difference in membrane properties (effective surface area and pore size) and the nature of the surface (flat vs patterned). The patterned membrane yields higher permeance in the tilted panel over the vertical one in all tests, being the highest at shortest filtration/relaxation cycle of 5 min, shortest switching period of 2.5 min and highest aeration rate of 1.5 L/min corresponding to permeances of 465 vs 409, 369 vs 318 and 447 vs 381 L/(m2h.bar), respectively. However, since operation with tilting only allows one-sided membrane, the patterned membrane offers better panel productivity when operated in a vertical panel. Operation with switching (intermittent aeration) only offers the slight advantage of panel productivity over the vertical one (546-738 vs 440-632 L/m2h.bar). Â© 2020 IOP Publishing Ltd.